2021
DOI: 10.1038/s41598-021-96525-y
|View full text |Cite
|
Sign up to set email alerts
|

Lack of gamma delta T cells ameliorates inflammatory response after acute intestinal ischemia reperfusion in mice

Abstract: T-cells have been demonstrated to modulate ischemia–reperfusion injury (IRI) in the kidney, lung, liver, and intestine. Whereas most T-cell subpopulations contribute primarily to the antigen-specific effector and memory phases of immunity, γδ-T-cells combine adaptive features with rapid, innate-like responses that can place them in the initiation phase of immune reactions. Therefore, we aimed to clarify the role of γδ-T-cells in intestinal IRI. Adult wild-type (WT) and γδ-T-cell-deficient mice were subjected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 45 publications
(59 reference statements)
1
13
0
Order By: Relevance
“…Selective depletion of γδ T cells after IRI significantly reduced proinflammatory cytokine levels and neutrophil infiltration in the intestinal tract compared with the control group. 196 In addition, γδ T KO delayed inflammatory reaction in early renal IRI, but with the extension of reperfusion time, the survival rate of knockout mice decreased. 194,197,198…”
Section: Ischemia-reperfusion Injurymentioning
confidence: 99%
See 2 more Smart Citations
“…Selective depletion of γδ T cells after IRI significantly reduced proinflammatory cytokine levels and neutrophil infiltration in the intestinal tract compared with the control group. 196 In addition, γδ T KO delayed inflammatory reaction in early renal IRI, but with the extension of reperfusion time, the survival rate of knockout mice decreased. 194,197,198…”
Section: Ischemia-reperfusion Injurymentioning
confidence: 99%
“…Importantly, recent studies in other IRI models also show that γδ T17 cells have a vital contribution to IRI 65,66,194–196 . For example, γδ T cells can be considered as mediators promoting the inflammatory response in the acute stage of intestinal IRI.…”
Section: Role Of γδ T17 Cells In Cvdmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al found that neutrophils and macrophages were recruited and activated as part of the first-line immune response in innate immunity against kidney disease induced by adenine in mice [63]. Moreover, Funken et al identified that the γδ-T cells as potent mediators in ischemia-reperfusion injury (IRI) contributed to the increased influx of neutrophils and pro-inflammatory cytokines, which were not found in δ-T cell deficiency mice [64]. IRI mouse model induced by bilateral renal pedicle clamping resulted in altered gut bacterial dysbiosis resulting in significant decreases in Lactobacilli, Ruminococacceae, and an increase in Enterobacteriaceae.…”
Section: Immunomodulatory Mechanisms Of Gut Microbiota In Ckdmentioning
confidence: 99%
“…In murine models, gamma delta T-cells are found within the infarct as early as Day 1 post-MI and peak at Day 7 post-MI [ 95 ]. Funken et al found that the loss of gamma delta T-cells in mice helped improve organ injury [ 96 ]. Through a gamma delta T-cell genetic depletion mouse model, Caillon et al discovered that this T-cell subset may also mediate vascular injury and activation of other T-cell subsets thus fostering an exacerbation of inflammation [ 97 ].…”
Section: Immune Cell Heterogeneity In the Heartmentioning
confidence: 99%